Limited Discectomy for single level lumbar disc herniation: a retrospective study in a tertiary level hospital (Bangladesh Journal of Medical Science, 2022)
Objective: To perform retrospective analysis of 1000 patients who underwent open limited discectomy (OLD) for single level lumbar disc herniation (LDH) and to assess the long- term clinical outcomes.Methods: 745 men and 255 women, with mean age of 38.03 ± 9.14 years (range 19- 55 years) who had primary LDH at L4-5 (n=640), L5-S1 (n=352), and L3-4 (n=8); underwent OLD were reviewed. Records were obtained regarding their demographic data, the side and level of disc herniation, operating time period, intraoperative blood loss, hospital stay, and perioperative complications. VAS score was measured before and after operation, for the assessment of low back pain (LBP) and radicular pain. Comprehensive outcome outcomes were measured postoperatively with the modified Macnab criteria and the Oswestry Disability Index (ODI) score.Results: The mean follows up was 24.5 (range 24-70) months. Significant improvement of mean VAS score for back and leg pain was achieved. At the two years follow-up, results were excellent in 525 (52.50%), good in 325 (32.50%), fair in 140 (14.00%) and poor in 10 (1.00%). Complications found were reherniation (n=52), discitis (n=19), superficial wound infection (n=7), dural tear (n=7) and foot drop (n=2).Conclusion: Open limited discectomy following fenestration or laminotomy is a safe and effective procedure and achieved favorable long-term outcome (e.g., low rate of recurrent LBP) and excellent patients’ satisfaction.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 37-44